Kapasitas Sumber Daya Kelurahan dalam Meningkatkan Pelayanan Publik Berbasis Informasi Geospasial - Putri, Rufia Andisetyana; Rini, Erma Fitria; Rahayu, Murtanti Jani; Andini, Isti (Regional Development Information Center, Universitas Sebelas Maret, 2017)
Information technology in the last ten years has become a necessity of public service. From the decision-making process to the digital display of data, information technology makes the storage, renewal and updating process much more efficient and easier to access. The dynamic utilization of urban space requires an efficient and easy-to-use database system. The purpose of this study is to determine the capacity of village resources as the front guard of planning in improving public services based on geospatial information. This study took places in Jebres and Pucangsawit sub-district. This research uses descriptive method to describe urban resource capacity in using geospatial information system. The results showed that 65% of the sub-district officers and 30% community have not been able to use geospatial information system properly. It shows that the capacity of human resources to run geographic information system in Jebres and Pucangsawit sub-districts are still need to improve.